(untitled) (Palíndromo, 2022)
This article aims to reflect the creative process of the artwork “Trans(embroideries) dreams”, created during the COVID-19 pandemic between 2020 and 2021. Throught autobiographical narrative and a/r/tographic methodology, the author narrates and reflects on research, artistic creation and the educational reverberations of her artwork to foster the idea of preserving the memory of dreams in her community. Free embroidery was the technique chosen for this “spider work” of building networks and also for the challenge of imagery representations, tangling text, textile art, dreams and utopias.